Evaluating Augmented Reality to Teach Science for Secondary Students With Intellectual Disability - Emrah Gulboy, PhD; Hicran Denizli-Gulboy
Augmented reality (AR) provides students with visual, auditory, and concrete learning understandings that facilitate their understanding of abstract concepts, leading to positive experiences in the learning process. Positive experiences increase students$1 (Bmotivation and interest in learning. This study examined the effects of using AR technology to teach science concepts. Three Turkish students with intellectual disabilities, between 12 and 13 years of age who were attending inclusive education, participated in the study. A multiple probe design across behaviors replicated across participants was used. The results indicated that all students acquired the science concepts, maintained the concepts 5 weeks later, and generalized the concept with classroom materials (science course textbook). Social validity results also showed that students found the AR intervention acceptable, making their learning experience more enjoyable. Conclusions are discussed in the context of applying universal design principles with AR technologies to create unique opportunities for students with intellectual disabilities to learn science concepts.s